Composite microsphere-functionalized scaffold for the controlled release of small molecules in tissue engineering - Pandolfi, Laura (J Tissue Eng, 2016)
Current tissue engineering strategies focus on restoring damaged tissue architectures using biologically active scaffolds. The ideal scaffold would mimic the extracellular matrix of any tissue of interest, promoting cell proliferation and de novo extracellular matrix deposition. A plethora of techniques have been evaluated to engineer scaffolds for the controlled and targeted release of bioactive molecules to provide a functional structure for tissue growth and remodeling, as well as enhance recruitment and proliferation of autologous cells within the implant. Recently, novel approaches using small molecules, instead of growth factors, have been exploited to regulate tissue regeneration. The use of small synthetic molecules could be very advantageous because of their stability, tunability, and low cost. Herein, we propose a chitosan–gelatin scaffold functionalized with composite microspheres consisting of mesoporous silicon microparticles and poly(dl-lactic-co-glycolic acid) for the controlled release of sphingosine-1-phospate, a small molecule of interest. We characterized the platform with scanning electron microscopy, Fourier transform infrared spectroscopy, and confocal microscopy. Finally, the biocompatibility of this multiscale system was analyzed by culturing human mesenchymal stem cells onto the scaffold. The presented strategy establishes the basis of a versatile scaffold for the controlled release of small molecules and for culturing mesenchymal stem cells for regenerative medicine applications.